Cytokine concentrations in basal cell carcinomas of different histological types and localization - Elamin, Issa (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
Background: Basal cell carcinoma (BCC) is the most common malignant skin tumor. Cytokines as major mediators of the immune system have been shown to play an important role in biology of the neoplasm with the general predomination of Th2 cytokines, whereas IFN-gamma and other Th1 cytokines are prevalent in spontaneously regressing tumors. Objective: We were interested incomparing cytokine levels in BCC and cutaneous squamous cell tumors with BCCof different localization and histological subtypes. Material and methods: Explants from freshly excised BCC from 18 patients, and cutaneous squamous cell tumors (solar keratoses and Bowenćs disease) from 9 patients were cultivated for 24 h. Cytokine (IL-2, IFN-gamma, IL-4, IL-5, IL-6, IL-8, IL-10,IL-12, TNFalpha, IL-1beta) concentrations in culture supernatants were determined by a sandwich immunoassay. Results: Tissue explants of BCC contained significantly higher concentrations of IL-1beta, IL-4, IL-5, and IL-6 compared to those of squamous cell tumors. Higher levels of TNF-alpha (p = 0.042), IL-4 (p = 0.028), and IL-5 (p = 0.012) were found in tumors localized to the head and neck compared to those on the trunk or extremities. Interleukin-6 concentrations were higher in aggressive BCC variants (infiltrative and micronodular), but the difference was not statistically significant (p = 0.068). Conclusions: Confirming the earlier findings that BCCis a tumor with a Th2 cytokine microenvironment, this study further shows that BCC situated on the head and neck produce even more of certain Th2 cytokines (IL-4 and IL-5) and TNF-alpha, a crucial immunosuppressive cytokine released upon UVB irradiation.
Keywords: Carcinoma, Basal Cell; Citokini; Cytokines; dermatologija; histologija; Interleukin-1; Interleukin-10; Interleukin-12; Interleukin-2; Interleukin-4; Interleukin-5; Interleukin-6; Interleukin-8; Interlevkin-1; Interlevkin-10; Interlevkin-12; Interlevkin-2; Interlevkin-4; Interlevkin-5; Interlevkin-6; Interlevkin-8; karcinom; Karcinom bazalnocelični; Kožne novotvorbe; rak (medicina); Skin Neoplasms; Tumor Necrosis Factor; Tumor nekrotizirajoči faktor